Prognostic utility of cardiovascular magnetic resonance upright maximal treadmill exercise testing. Issue 1 (December 2015) - Sukpraphrute, Bunyapon; Drafts, Brandon; Rerkpattanapipat, Pairoj; Morgan, Timothy; Kirkman, Paul; Ntim, William; Hamilton, Craig; Cockrum, Robert; Hundley, W.
Abstract Background Left ventricular wall motion abnormalities (LVWMA) observed during cardiovascular magnetic resonance (CMR) pharmacologic stress testing can be used to determine cardiac prognosis, but currently, information regarding the prognostic utility of upright maximal treadmill induced LVWMA is unknown. Our objective was to determine the prognostic utility of upright maximal treadmill exercise stress CMR. Methods One hundred and fifteen (115) men and women with known or suspected coronary arteriosclerosis and an appropriate indication for cardiovascular (CV) imaging to supplement ST segment stress testing underwent an upright treadmill exercise CMR stress test in which LVWMA were identified before and immediately after exercise. Personnel blinded to results determined the post-test incidence of cardiac events (cardiac death, myocardial infarctions [MI], and unstable angina warranting hospital admission or coronary arterial revascularization). Results All participants completed the testing protocol, with 90 % completing image acquisition within 60 s of exercise cessation. MI or cardiac death occurred in 3 % of individuals without and 17 % of individuals with inducible LVWMA (p  = 0.024). The combination of MI, cardiac death, and unstable angina warranting hospitalization occurred in 14 % of individuals without and 47 % of individuals with inducible LVWMA (p  = 0.002). The addition of CMR imaging identified those at risk for future events (p  = 0.002), as opposed to the electrocardiogram stress test alone (p  = 0.63). Conclusions In patients with or suspected of coronary arteriosclerosis and appropriate indication for imaging to supplement ST segment analysis during upright treadmill exercise, the presence of inducible LVWMA during treadmill exercise stress CMR supplements ST segment monitoring and helps identify those at risk of the future combined endpoints of myocardial infarction, cardiac death, and unstable angina warranting hospitalization.